Relay Selection with Threshold Value for DF Based Cooperative Systems - Aydin, Erdogan; Ilhan, Haci (IEEE, 2015)
In this paper, a cooperative system structure that utilizes decode and forward (DF) method with relay selection based on the optimum relaying strategy have been proposed. The source-relay, relay-destination and source destination links are modeled as Nakagami-m distributed random variables. In order to decrease performance degradation due to error propagations in DF based wireless cooperative networks and increase the error performance of the system, virtual noise (VN), MRC and cooperative-MRC based detection techniques with the optimal threshold value are considered. Optimum threshold value functions of the considered techniques are derived theoretically.
Keywords: Cooperative diversity; relay selection; SNR based selection relaying; virtual noise; Nakagami-m fading; PERFORMANCE; DIVERSITY; NETWORKS; Engineering; Telecommunications